THE TRAINING FOR THE RETIREMENT: REVISION OF THE SOCIAL AND PSYCHOLOGICAL FACTORS THAT INCISE IN A BETTER EMOCIONAL ADJUSTMENT ON LABOUR PERFORMANCE END - Madrid García, Antonio José; Garcés de los Fayos Ruiz, Enrique Javier (Anales de Psicología / Annals of Psychology, 2000)
In this work we present a revision about the socialand psychological different aspects that are associatedto professional conditions of retirement. First, we describethe factors which are in the origin of the perceptions thatthe worker shows about the retirement, as well as the instrumentsthat have been usually utilized for these factorsevaluation, and the negative psychological character consequencesthat can be valued in the people who don´t adaptwell to the retirement. Likewise, we present a well emocionaladjustment analysis of the people who retire and theprocesses that explain the satisfaction perception that particularworkers feel.We finish presenting an structure of formative accionfor improve the retirement adjustment and adaptation, aswell as the most outstanding conclusions and future researchlines.